The image of Al-Salamiyah Saudi Club presented through its digital accounts on the Internet: An analytical study (The International Journal of Educational Sciences and Arts, 2025)
The study aims to identify the image of the Saudi Al-Salmiya Club as presented through its digital accounts on the Internet, and to monitor the attraction elements used in the posts published on the club’s digital platforms. It also seeks to determine the objectives behind presenting various topics and issues via Al-Salmiya Club’s digital accounts on the Internet.The study is classified as a descriptive study and relies on the media survey method. The sample consisted of analyzing 78 tweets published on the official X-platform account of Al-Salmiya Club during the period from October 1, 2025 to October 31, 2025, using content analysis as the tool for data collection.The study reached several key findings, the most important of which are:-   The features of the club’s presented image reflect a generally positive mental image of Al-Salmiya Club. The feature “sharing information with the audience” ranked first among the image traits portrayed through the club’s account on X, followed by “credibility of the presented information” in second place, while “diversity of activities and content” ranked third.-   Al-Salmiya Club’s account on X primarily sought to “provide information” to its audience, with this objective ranking first at 66.7% among the goals of topic presentation. It was followed by the goal of “enhancing the club’s image” in second place at 15.4%, and “entertainment and amusement” in third place at 10.2%.-   Sports events topped the list of topics presented on Al-Salmiya Club’s account, constituting 41% of the content analyzed. This was followed by team training activities in second place at 28.2%, and the club’s social activities in third place at 11.5%.
Keywords: Al-Salmiya Club; Internet; Mental Image; X Platform